2011
DOI: 10.1039/c0cp02296a
|View full text |Cite
|
Sign up to set email alerts
|

Patchy colloids: state of the art and perspectives

Abstract: Recently, an increasing experimental effort has been devoted to the synthesis of complex colloidal particles with chemically or physically patterned surfaces and possible specific shapes that are far from spherical. These new colloidal particles with anisotropic interactions are commonly named patchy particles. In this Perspective article, we focus on patchy systems characterized by spherical neutral particles with patchy surfaces. We summarize most of the patchy particle models that have been developed so far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
462
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 439 publications
(465 citation statements)
references
References 148 publications
3
462
0
Order By: Relevance
“…One approach is to decorate the surface of colloidal particles with "sticky patches," made, for example, of synthetic organic or biological molecules and assigned to specific locations [15][16][17][18][19] . Bonding between particles occurs through patch-patch interactions, so that in principle the location and functionality of the patches can endow particles with bonding directionality and valence.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to decorate the surface of colloidal particles with "sticky patches," made, for example, of synthetic organic or biological molecules and assigned to specific locations [15][16][17][18][19] . Bonding between particles occurs through patch-patch interactions, so that in principle the location and functionality of the patches can endow particles with bonding directionality and valence.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 5 we have depicted U ⋆ and η (both obtained via simulations) along the isotherm T ⋆ = 0.10 over a relatively large pressure interval, namely P ⋆ ∈ [2,10]. Values for the two quantities are depicted for structures labeled "b", "d", "e", "f", "g", and "h" over the respective ranges of stability; we note that mechanical stability (i.e., a positive compressibility) is guaranteed as long as η increases monotonically with increasing pressure.…”
Section: Structural Variations Along Isothermsmentioning
confidence: 99%
“…Patchy particles are colloidal entities whose surfaces are decorated by well-defined regions, which differ in their interaction behaviour significantly from the one of the "naked" colloidal surface (for an experimental and theoretical overview see [1] and [2], respectively). Since these regions can be positioned with high accuracy on the particle surface and the spatial extent of the patches can be tuned in suitable chemical or physical synthesis processes, the highly directional and selective interactions of patchy particles have promoted them as very promising entities that are able to self-assemble into larger target units with desired physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…A beautiful review on the experimental methods to produce patchy particles can be found in the paper of Bianchi et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…We map the phase space for a range of values of the interaction potential and for two different forms of the interaction potential. We have chosen as subunits patchy particles, because in addition to mimicking the properties of hydrogen bonds, they have a rich ensemble of self-assembling properties [11][12][13].…”
Section: Introductionmentioning
confidence: 99%